Macroeconomic modelling for policy analysis - Ghezzi, Leonardo; Bardazzi, Rossella (Studi e saggi, 2013)
Over the last 30 years, the Inforum approach to macro modelling has been shared by economists worldwide. Researchers have focussed much of their efforts to developing a linked system of international interindustry models with a consistent methodology. A world-wide network of research associates use the same methods and software obtaining comparable results. The XXth Inforum World Conference was held in Florence in September 2012 and this book contains a selection of papers presented during that Conference. All these contributions are aimed at policymakers, stakeholders, and applied economists. Some papers are devoted to specific topics (total factor productivity, energy issues, external linkages, demographic changes) and some others are oriented to macro model building and simulations.